Iodine Nutritional Status among Lactating Mothers of Murshidabad District in West Bengal (International Journal of Food and Nutritional Sciences, 2022)
In post salt iodization phase, endemic goiter was found prevalent all over the India including West Bengal. Prevalence of goitre among school children and pregnant women has been reported in Murshidabad district. But iodine nutritional status and prevalence of goitre along with associated iodine deficiency disorders of lactating mother has not been reported in the Murshidabad district of West Bengal. In total, 543 lactating mothers (aged between 18-40 yr) were clinically examined for goitre from five Sub divisions of Murshidabad district. The overall goitre prevalence was found to be 13.1%. Most of the goitre was palpable (grade 1) however visible goitre (grade 2) also existed. In the studied population, post prevalent abnormalities were feeble mindedness (41.6%), followed by deaf mutism (13.1%), squint (1.5%), miscarriage (5.9%) and stillbirth (1.7%). Urinary iodine and thiocyanate concentrations were measured for all subjects and the mean urinary iodine and mean urinary thiocyanate levels were found to be 12.6±8.9 µg/dl and 0.610±0.21 mg/dl. The overall observations suggest that lactating mothers of the studied region of Murshidabad district in West Bengal are affected by goitre as per clinical investigation. But urinary iodine excretion pattern shows that there was no biochemical iodine deficiency. The people of the studied region consume foods containing thiocyanate precursors as evidenced by urinary thiocyanate excretion pattern. Thus inspite of the consumption of adequate iodine, existing goitre prevalence may be due to the consumption of dietary goitrogens/antithyroid substances that possibly come through food and water.